Fabrication, Mechanical Characterization, and Ranking of Shell Ash Reinforced Al-7075-Based Hybrid Composites - E. V. Ratna Kumar G.; Senthil Kumar K.; Ranga Babu J. A. (Журнал інженерних наук)
In the research article, the fabrication of Al-7075-based hybrid composites was done by stir casting technique with the addition of a mixture of crab shell ash (CSA), oyster shell ash (OSA), and snail shell ash (SSA). The mixtures of CSA, OSA, and SSA (MCOSA), CSA and OSA (MCOA), CSA and SSA (MCSA), as well as OSA and SSA (MOSA) with weight percentages in a range of 1–3% were added to the base material. The specimens were prepared according to the ASTM standards and tested for mechanical properties. The hardness, as well as impact, flexural, and tensile strengths of the composites, were increased as the amount of reinforcement to the base metal was increased, and compressive strength was decreased. The greatest tensile strength, tensile modulus, and compressive strength values were observed for the composite designated with AlOSA3. The maximum flexural strength and hardness values were observed for the compositions AlOS21 and AlCO12, respectively. Two techniques (TOPSIS and VIKOR) were successfully applied to the mechanical attributes of composites. The ranking results of both methods were compared. The ranking results for TOPSIS and VIKOR were the same for the index value 0.25. The composites filled with aquatic waste fillers can be used for automotive applications concerning their enhanced mechanical properties compared to the Al-7075 metal alloy properties.